Characterization of the minority volatile fraction of alcoholic fermented beverage from jabuticaba (Plinia jaboticaba) by CG / MS (Research, Society and Development, 2021)
The volatile composition is extremely important to the quality of alcoholic beverages, as it directly influences its aroma. There are few studies on the volatile composition of untraditional alcoholic beverages, including beverages made from jabuticaba. This work has the objective of identifying the minority volatiles compost, by CG / MS, in alcoholic fermented beverage from jabuticaba. Were identified 78 volatile compounds, among alcohols, esters, furans, organic acids, aldehydes and ketones, acetates, terpenes, volatile phenolic compounds and lactones. The characterization of the volatile fraction of alcoholic fermented beverage from jabuticaba resulted in a large number of data that, due to its extension and novelty, may contribute to future works that aim to improve the quality of this beverage.